2020
DOI: 10.4067/s0717-95022020000300706
|View full text |Cite
|
Sign up to set email alerts
|

The Morphometrics and Typology of the Skull in the Ghanaian Local Dog of Non-Descript Breed (Canis lupus familiaris)

Abstract: The Morphometrics and Typology of the Skull in the Ghanaian Local Dog of NonDescript Breed (Canis lupus familiaris) Morfometría y Tipología del Cráneo en el Perro Local de Ghana de Raza no Definida (Canis lupus familiaris

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
4
1
Order By: Relevance
“…The present results showed that the skull index of the Baladi dogs ranged from 50.69 – 52.86 indicating that they belong to the mesocephalic type [ 61 ]. In addition, the skulls of the Baladi dog in the current study had higher values of skull length, width, palatine length, and mandibular length than those of the local Nigerian dogs [ 62 ] and local Ghanaian dogs [ 52 ], but had lower values of skull length, width, and height, and cranial, facial, and palatine length than that reported in the adult male Kangal dogs [ 34 ]. Moreover, the Baladi dog in the present study had higher values of skull length and nasal length but lower values of cranial length and cranial width than those reported in the Iranian mixed breed dogs [ 27 ].…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…The present results showed that the skull index of the Baladi dogs ranged from 50.69 – 52.86 indicating that they belong to the mesocephalic type [ 61 ]. In addition, the skulls of the Baladi dog in the current study had higher values of skull length, width, palatine length, and mandibular length than those of the local Nigerian dogs [ 62 ] and local Ghanaian dogs [ 52 ], but had lower values of skull length, width, and height, and cranial, facial, and palatine length than that reported in the adult male Kangal dogs [ 34 ]. Moreover, the Baladi dog in the present study had higher values of skull length and nasal length but lower values of cranial length and cranial width than those reported in the Iranian mixed breed dogs [ 27 ].…”
Section: Discussioncontrasting
confidence: 51%
“…In consistence to the present result, the widest part of the red fox palate is located at the level of the caudal border of the upper fourth premolars [ 51 ]. In contrast, the widest part of the palate is located at the level of the first molar tooth in Ghanaian dog [ 52 ]. Similar to the current findings, the permanent dental formula of the red fox, Baladi dog, and Iberian wolf is I 3/3, C 1/1, P 4/4, M 2/3 [ 53 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The width average of the Deltari Ilir skull, which was 124.29 ± 8.93 mm in females and 129.65 ± 8.25 mm in males, showed that we are dealing with a dog with a large skull size, probably one of the largest compared with studies conducted by Onar et al, 2001 in the male Kangal dog where the skull length was 258.73 ± 13.357 mm and width was 130.03 ± 5.404 mm, or in the study made by Daskiran and Cedden (2006) in the skull length of Kangal dog was 23.773 ± 0.308 cm in females and 24.750 ± 0.374 cm in males and skull width(between two zygomatic archs) 13.091 ± 0.202 cm and 14.844 ± 0.197 cm in female and males respectively. In the study made by Igado (2017) in Nigerian local dog the skull length was 15.8 ± 1.1 cm in females and 16.64 ± 1.647 cm in males but, in the study made by Urosevic et al (2020) in Akbaş Turkish Shepherd Dog the skull length in females was 16.00 ± 1.58 cm and 17.00 ± 2.16 cm in males but the skull width was 13.63 ± 2.28 cm and 14.06 ± 1.96 cm in females and males, respectively, whereas in the study performed by Opoku‐Agyemang et al (2020) the skull length of Ghanian local dog resulted from 18.535 ± 1.977 cm to 22.847 ± 0.927 cm and males and finally in the study of İlgün et al (2022) made in the Aksaray Malakli dogs the skull length was 245.78 ± 15.35 mm.…”
Section: Discussionmentioning
confidence: 87%
“…The skeleton of the animal's head and especially the skeleton of the skull in the dog is a very important and valuable element in determining the type of animals, breeds, ages and even their sex. This is based on numerous osteometry studies performed on many species of the Canidae family such as Onar (1999), Onar et al (2001, 2005), Daskiran and Cedden (2006), Monfared (2013), Rezić et al (2017), Opoku‐Agyemang et al (2020), İlgün et al (2022), Srinivas and Jhala (2021), who have evaluated the morphology of the skull, have shown many different morphometric parameters and have calculated different types of indices in order to estimate the typology of the skull, breed, age and sex.…”
Section: Discussionmentioning
confidence: 99%